The Influence of Financial Literacy and Financial Inclusion on the Financial Performance of MSMEs with Digital Finance as a Mediating Variable - Dela Sari; Endang Kristiawati; Aris Setiawan (International Forum of Researchers and Lecturers, 2026)
This research seeks to obtain empirical evidence regarding the influence of financial literacy, financial inclusion, digital finance and financial performance of MSMEs in Pontianak City. The main problem that is often faced by MSME actors is the limitation in understanding related to financial management. Many business actors do not have the ability to carry out systematic financial recording, financial planning, and proper financial decision-making. The financial performance of MSMEs is an important indicator in assessing the success of a business in managing its financial resources. This research seeks to analyze the influence of financial literacy and financial inclusion on the financial performance of MSMEs with digital finance as a mediating variable. The Partial Least Square (PLS) method of data analysis was used to examine the association between variables. This study is an explanatory quantitative research designed to analyze the causal relationship between financial literacy and financial inclusion on the financial performance of MSMEs, with digital finance as a mediating variable. The results of the study are expected to provide a deeper understanding of the factors that affect the financial performance of MSME actors in Pontianak City.